Podcast Multimedia in Inquiry Learning: Fostering Environmental Awareness and Attitudes for Geography Students - Risa Amalia Kurniawati; Sumarmi; Alfyananda Kurnia Putra; Yuswanti Ariani Wirahayu (Universitas Negeri Surabaya, 2024)
This research is purposely to discover the influence of inquiry learning model with assistance of podcast based learning media in increasing the awareness and environmental care for geography students. Additionally, this research is done to know the difference of student activity between the class that uses inquiry learning model assisted by podcast and the class that uses conventional learning model. This research uses quasi-experimental design. The data was collected using awareness and environment care in pretest and posttest in experiment and control classes. The selected population is students of Muhammadiyah 2 Genteng High School Banyuwangi of 2021/2022 school year in social studies faculty. Experiment group originated from XI IIS class and control group originated from XI 2 IIS class with 60 students in number. Data was analyzed using ANCOVA with SPSS 25 version software for Windows. Results of this research proved that inquiry learning model with assistance of podcast has significant influence towards shifting of awareness and environment care of geography students. The student activities in experiment class is more active in comparison to those in control class.